Effect of crude extracts from the root of Stemona tuberosa Lour. on the replication of Autographa californica multiple nucleopolyhedrovirus - Petcharawan Ounruan; Thanaboripat Dusanee; Karunasoong Tippanya; Chalernsuk Kunlanit; Sakolvaree Jira (My University, 2016)
The purpose of this research was to investigate the effect of crude extracts from the root of Stemona tuberosa Lour. on the replication of Autographa californica multiple nucleopolyhedrovirus (AcMNPV). Cytotoxicity of crude hexane, dichloromethane and ethanol extracts from the root of S. tuberosa was tested against Spodoptera frugiperda cell line (Sf9) using MTT assay. The cytotoxic effect, represented as CC50 (µg/ml) was observed after 48 and 96 h. It was shown that dichloromethane extract was more toxic than hexane and ethanol extracts and 96-h CC50 for the dichloromethane extract was 1,708.98 µg/ml. Crude dichloromethane extract at the concentration of 31.25 µg/ml was then tested on AcMNPV. The extract was added after 1 h post-infection of AcMNPV at the multiplicity of infection (MOI) of 2, in Sf9 cell line cultivated in vitro. No significant difference between the percentage of infected cells in the control and the test sample with crude dichloromethane extract was found. The average number of polyhedra (OBs/ml) in the control (5.11×106±0.63 OBs/ml) was not significantly different from the test sample (4.19×106±0.31 OBs/ml). However, there was significant difference between the average virus titer (budded virus, BV) in the control (2.06×108±0.71 PFU/ml) and the test samples (2.65×108±0.79 PFU/ml). Crude dichloromethane extract (31.25 µg/ml) did not toxic to Sf9 cells but it could enhance AcMNPV replication in Sf9 cell line cultivated in vitro. It could be concluded that S. tuberosa can be a good candidate for developing the insect virus production in vitro for controlling insect pests. Key words:  AcMNPV, crude extract, cytotoxicity test, by 3-(4, 5- dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay.
Keywords: Dichloromethane; Sf9; Autographa californica; Hexane; Negative control; Advanced Synthetic Organic Chemistry